2012
DOI: 10.21059/buletinpeternak.v33i3.114
|View full text |Cite
|
Sign up to set email alerts
|

Kualitas Organoleptik Daging Kambing Lokal dengan Lama Pelayuan dan Cara Pemasakan yang Berbeda (Sensoring Quality of Lokal Goat Meat as Influenced by Different Length of Conditioning and Types of Cooking)

Abstract: <p>The aim of this research was to study the effect of different length of conditioning time and types of cooking on sensory quality of meat from goats under traditional way of keeping in remote villages. The result of this research would lead to the ability to decide the better conditioning processes post slaughtering to increase meat quality. The research was done following a completely randomized design of 4x2 factorial, each combination of experimental treatment had three replications. The first fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Studies have shown that various cooking methods have various impacts on the aromatic and flavor profile of lamb meat, contributing to increased taste and odor [81]. Compared to boiling, roasting is more acceptable and improves the quality of juiciness, taste, and aroma [78]. The effect of the cooking method on goat meat in Indonesia has been reported [82]; goat meat satay grilled for 7 min resulted in a low quality of flavor, while goat meat satay grilled for 3 min was more acceptable.…”
Section: The Effect Of Different Post-mortem Processing Methods On Th...mentioning
confidence: 99%
“…Studies have shown that various cooking methods have various impacts on the aromatic and flavor profile of lamb meat, contributing to increased taste and odor [81]. Compared to boiling, roasting is more acceptable and improves the quality of juiciness, taste, and aroma [78]. The effect of the cooking method on goat meat in Indonesia has been reported [82]; goat meat satay grilled for 7 min resulted in a low quality of flavor, while goat meat satay grilled for 3 min was more acceptable.…”
Section: The Effect Of Different Post-mortem Processing Methods On Th...mentioning
confidence: 99%